The effect of cost of credit on money demand: empirical evidence from Malaysia - Azali, M.; Habibullah, Muzafar Shah; Jalal, M.Y. (Universiti Utara Malaysia, 2001)
This paper investigates the dynamic of long-run relationship between cost of credit and real money balances in Malaysia. The Johansen-Juselius (1990) likelihood ratio tests support the importance of the cost of credit in the real broad money demand function. The sample period spans from 1978:q1 through 1997:q4. The results provide empirical evidence for the long-run relationship between cost of credit and broad money balances in Malaysia.